Finite element analysis of braced excavation in nonuniform soils - Heng, Zheng Yan (Nanyang Technological University, 2022)
Numerous studies have been carried out for braced excavations in sand or soft/stiff clays individually, but there are limited studies on nonuniform soils consisting of soft clay over-lying a stiff clay layer. The study of the effects of various parameters, such as the thickness of the soft clay layer, stiffness of the wall system and the number of strut levels, on the strut forces, maximum ground settlement behind the wall, and the maximum wall deflection are investigated using the finite element analysis software, Plaxis 2D. The Hardening-Soil model was used to model the stress-strain behaviour of the soils.